Estudio de pre factibilidad para la producción de zapallo cucúrbita máxima en el cantón Arenillas y su comercialización al mercado externo - Sanmartìn Espinoza, Manuel Lizandro (2014)
The pumpkin (Cucurbita maxima D) is a plant native to America. The pumpkin is a fruit of high nutritional value, have high amounts of vitamins and minerals such as phosphorus, iron and calcium. It has less than 10 % carbohydrate, low in fat, 1.1 % of nitrogen compounds and crude fiber 1.6%. It is valuable also for the content of carotenoids (β - carotene, α -carotene and lutein) potassium, vitamins B2, C and E and has a low content heat (CLIMB PLA et al, 2007; Gebhardt and Thomas, 2002; GONZÁLEZ et al, 2001; RODRIGUEZ AMAYA, 1997).The purpose of the pre-feasibility study is to provide concerned sufficient information to demonstrate the advisability of investing in a product. The decision to invest should be performed after each investor complete a feasibility study, with relevant information for its own operation, as the growing area, ground condition, distance to the water source, availability of capital, among and others.The purpose of market research using secondary data sources, such as trade statistics in the region and product, helped us find two concerns simultaneously. First, if you intend to sell the product is consumed in the target market. Second, the product consumed, about which onepresentation is most widely accepted by the consumer.Based on the variables discussed above, Germany is a target market in which we identify a good opportunity for our marketing fresh pumpkin.The objective of the survey was to collect information that will feed cost structures of reference. These were aimed at two groups of people: the farmers and input dealers. In the first case, the survey inquired quantities used in the production process, the value of wages, the provision of equipment and technical assistance, among others. In the second case, the sellers asked for the price of agricultural inputs used in production, this in order to unify the price of agri-inputs to be used for the calculation of reference costs in each area.The calculation methodology for the economic sought study to determine the weight that each of the activities in the total cost per hectare. In other words, allowed to establish the appropriate cost structure for activity. This all added manpower, supplies and other expenses of each of the activities and for each the cost per hectare is calculated, giving as a result $ $ 4 399,03; grossed $ 5 600,97, a unit cost of $ 0,44 per pumpkin, and a financial indicator that indicates that for every dollar invested additional $ 0,88 will recover.